Tetrazolium test in timbaúba seeds - Nogueira, Narjara Walessa; Torres, Salvador Barros; Freitas, Rômulo Magno Oliveira de (Semina: Ciências Agrárias, 2014)
The tetrazolium test has shown itself to be a promising alternative in determining the viability and vigor of seeds of forest species by the quality and speed of data collection. Thus, this paper was developed with the goal of standardizing the methodology for conducting the tetrazolium test for assessing the physiological quality of seed lots Timbaúba. To evaluate the physiological quality of seeds the four lots were subjected to the following determinations: water content, germination, first count and speed germination. Four replicates of 25 seeds from each batch were submerged in tetrazolium solution and kept in the dark at 35 Â°C for periods of 1, 3 and 6 hours under concentrations of 0.1, 0.075 and 0.050%. After the staining periods, the seeds were washed, split lengthwise between the cotyledon and ranked in viable and not viable. Seed exposure for periods of one hour and six hours has proved inadequate for driving the tetrazolium test since not promoted the proper interpretation of staining results. The tetrazolium test is a viable alternative for the evaluation of existing lots of Timbaúba. To conduct the test recommended scarification followed by soaking the seeds in water for 24 hours and coat removal, with subsequent soaking of seeds for three hours in tetrazolium solution of 0.075 % at 35 ºC.